Useless Landscape: Dense and Opaque Drawings - Paula, Carlos Eduardo Ferreira (Revista do Colóquio, 2025)
The essay presents a reflection on the series “Useless Landscape” (2022), composed of drawings made with asphalt paint on tracing paper. The works record direct gestures, evoking geological formations and exploring the relationship between matter, time and procedure. Inspired by Raymond Roussel’s concept of “procedure”, the series investigates the limits of drawing as a creative process. The embodied images affirm the vitality of art beyond its material existence. The parallel textual production is integrated as an unfolding of the work, expanding its field of meaning. The work thus reveals an artistic practice that unites gesture, body and language.